By the side of the oppressed. Enrica Collotti Pischel between historical research and political commitment (Altre Modernità, 2024)
Since the beginning of the Fifties Enrica Collotti Pischel introduced in Italy the study of contemporary China trying to describe and explain the nature and characteristics of the current political and social processes, from the construction of socialism to the cultural revolution. In the same way she helped to raise awareness of the Vietnam War, taking the side of the Vietnamese and all those over the world she believed were the ‘oppressed’.
Keywords: Decolonization; China; Vietnam; War; Collotti Pischel